Cooperation of Transmigration Community with Local Communities in Alur Village, Tanah Laut Regency - Purnomo Purnomo; Herry Porda Nugroho Putro; M. Zaenal Arifin Anis (Postgraduate Program - Lambung Mangkurat University (ULM Press Academic), 2018)
The background of this research is the economic cooperation between the transmigration community and the local community, form of the economic cooperation, and factors driving and inhibiting the economic cooperation between transmigration community and the local community. The purpose of this research is to identify the economic cooperation, to describe the form of the economic cooperation, and to describe factors driving and inhibiting the formation of the economic cooperation between the transmigration community and the local community in Alur Village. This study used qualitative method and techniques of data collection are observation, interviews, and documentation. Through the qualitative approach, the researcher can perceive a social reality which is holistic or as a whole, complex, dynamic and full or meaning. Qualitative method in its use is to examine the condition of a natural object where the researcher works as the key instrument.The result showed that in fact the economy income of the transmigration community comes from agriculture (food crops), plantations (rubber) and corps (grain crops and vegetables) while the income of the local community comes from agriculture (food crop cultivation on dry land), and the nature availability around the village of Alur. The cooperation between the transmigration community and the local community associations in the forms of social gatherings and mutual helps.